Ion Implantation Research and Application - Ahmad, Ishaq (IntechOpen, 2017)
Ion implantation is one of the promising areas of sciences and technologies. It has been observed as a continuously evolving technology. In this book, there is a detailed overview of the recent ion implantation research and innovation along with the existing ion implantation technological issues especially in microelectronics. The book also reviews the basic knowledge of the radiation-induced defects production during the ion implantation in case of a semiconductor structure for fabrication and development of the required perfect microelectronic devices. The improvement of the biocompatibility of biomaterials by ion implantation, which is a hot research topic, has been summarized in the book as well. Moreover, advanced materials characterization techniques are also covered in this book to evaluate the ion implantation impact on the materials.